A Transporter Motor Taken Apart: Flexibility in the Nucleotide Binding Domains of a Heterodimeric ABC Exporter. - Bukowska,MA; Hohl,M; Geertsma,ER; Hürlimann,LM; Grütter,MG; Seeger,MA (Biochemistry, 2015)
ABC exporters are ubiquitous multidomain transport proteins that couple ATP hydrolysis at a pair of nucleotide binding domains to substrate transport across the lipid bilayer mediated by two transmembrane domains. Recently, the crystal structure of the heterodimeric ABC exporter TM287/288 was determined. One of its asymmetric ATP binding sites is called the degenerate site; it binds nucleotides tightly but is impaired in terms of ATP hydrolysis. Here we report the crystal structures of both isolated motor domains of TM287/288. Unexpectedly, structural elements constituting the degenerate ATP binding site are disordered in these crystals and become structured only in the context of the full-length transporter. In addition, hydrogen bonding patterns of key residues, including those of the catalytically important Walker B and the switch loop motifs, are fundamentally different in the solitary NBDs compared to those in the intact transport protein. The structures reveal crucial interdomain contacts that need to be established for the proper assembly of the functional transporter complex.